Increasing Students’ Vocabulary by Using Song Lyrics - Ngongo, Mariana; Astuti, Endang S; Tities Hijratur Rahmah (UIBU, 2023)
This study aims to improve the vocabulary acquisition and learning activeness of the tenth-grade students of SMAN I Tana Righu through the implementation of song lyrics as a learning medium, utilizing the Classroom Action Research (CAR) method. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection. Data were collected through vocabulary tests, observation sheets, and student questionnaires. The findings indicate a significant increase in the average student vocabulary scores and the level of student participation in learning activities across the cycles. The success criteria, defined as 75% of students achieving a minimum score of 70, were met in Cycle II. The use of song lyrics effectively provides a fun, authentic, and contextualized learning environment, leading to improved student motivation and vocabulary mastery.